PENGARUH ALAT PERMAINAN EDUKATIF LOGICO TERHADAP PENINGKATAN KEMAMPUAN LOGIKA MATEMATIKA - Cecilia Kristanto (IKIP Siliwangi, 2016)
This research is motivated by the fact that in general in the learning process in classes conducted by the teacher just focus on conventional learning activities by using a written worksheet commonly referred to as Student Worksheet (LKS). The teachers haven’t optimize the use of other learning media in the classroom. One way to improve the ability of mathematical logic in early childhood, especially in children kindergarten is by using learning media tool, educational games. So in this research Logico educational games is used in order to make learning prosess more interesting and varied. The purpose of this study is to improve mathematical logic abilities of teh students through Logico educational games. This study is a quantitative research, with quasiexperimental research design. Subjects in this study were 17 to 24 students of kindergarten group B aged 5-6 years of Saint Aloysius School, in the academic year 2015/2016. Data collection techniques in this research are observation and documentation. This study showed that by using Logico educational games there is an increase in mathematical logic abilty. The results of hypotheses testing by t-test of pre-test of the experimental group and the control group showed no significant difference. Improvementin the mathematical logic experimental group was greater than in the control group. The implication of research is that Logico educatinal games can improve the ability of mathematical logic and learning process in the classroom can become more interesting and not boring for young students. It can be concluded that Logico educational games is more effective than the Student Worksheet (LKS).Through the result of this research the kindergarten teachers are expected to understand and utilize the Logico educational games that increase.Keywords: mathematical logic ability, Logico educational games